Educating Pancasila Values To The Digital Generation In Facing The Society 5.0 Era - Supriyono, Supriyono; Nugraha, Dadi Mulyadi; Supriatna, Aang; Islamy, Mohammad Rindu Fajar (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Technology is now inseparable from society, including the field of education. Currently, students can be said to be dependent on technology in their learning process, and they are proficient in using technological devices. Due to this dependency, they are referred to as the digital generation or the internet generation. Generation Z is known for their multitasking abilities, which align with the emergence of the Society 5.0 era, first introduced in Japan by Prime Minister Shinzo Abe, referring to a super-smart society that digitizes not only the economic and industrial sectors but all aspects of life. In Indonesia, Pancasila and Civic Education are fields of study that teach nationalism and how to be law-abiding Indonesian citizens. The digitalization across various fields in the upcoming future poses a unique challenge for the effectiveness of teaching Pancasila and Civic Education, as technological advancements are often perceived to erode nationalism among the younger generation. The research method and approach used is library research, which involves gathering data from books, journals, articles, and other reading sources. The research demonstrates that technology can enhance the teaching of Pancasila and Civic Education to be more effective using methods preferred by the current generation.